Obtaining and Characterization of the Monoclonal Antibodies Against G-Protein of the Respiratory Syncytial Virus - N. A. Demidova; R. R. Klimova; A. A. Kushch; E. I. Lesnova; O. V. Masalova; A. D. Dorofeeva; A. A. Nikonova; N. E. Fedorova; V. V. Zverev (Журнал микробиологии, эпидемиологии и иммунобиологии, 2020)
The aim of this study was to obtain hybridomas producing monoclonal antibodies (Mabs) to the G-protein of the respiratory syncytial virus (RSV), and to evaluate their immunological characteristics and virus-neutralizing activity.Material and methods. Mouse Mabs were obtained using hybridoma technology. The properties of Mabs were studied by enzyme-linked immunosorbent assay (ELISA), immunofluorescence staining (IF) of infected cells, as well as by biological neutralization test in vitro (NT). To identify epitopes recognized by the Mabs on G protein ELISA additivity test was used.Results. Hybridization of splenocytes with Sp2/0 myeloma cells and primary screening showed that 75 hybridomas produce antibodies interacting with purified virus, 17 of them also react with the recombinant G-protein in ELISA. In NT 4, hybridomas suppressed in vitro RSV infection by more than 50%. Cloning of these hybridomas revealed 4 monoclones producing the most active Mabs. Mab 1C11 was IgG2a, 3 others (5D4, 5G11 and 6H4) were IgM. Three IgM Mabs actively reacted with both RSV A2 and Long, and with G-protein; Mab 1C11 was less reactive with all antigens tested. All Mabs suppressed RSV infection, while Mab 5D4 supressed it almost completely (98%). IF analysis showed that all Mabs detected RSV G-protein in the cell cytoplasm, the largest number of infected cells was detected using Mab 5D4 (80%). It was shown that the isolated Mabs were directed to two non-overlapping epitopes on the RSV G-protein.Conclusion. The isolated Mabs can be used to detect RSV in clinical samples by ELISA and IF. The isolated Mabs can be used for humanized recombinant antibodies construction and for the treatment of RSV infection in future.